Hardiness pada Ibu dengan Anak Autism Spectrum Disorder - Zakiyah, Abidatuz; Masfufah, Ulfa (Universitas Negeri Malang, 2025)
Parenting a child with Autism Spectrum Disorder (ASD) poses significant emotional and practical challenges for mothers as primary caregivers. This study aims to describe hardiness in mothers who have children with ASD and explain the contribution of hardiness to coping strategies used in facing parenting challenges. The study used a phenomenological approach with three mothers as subjects, selected through a purposive sampling technique. Data were obtained through in-depth interviews and analyzed using the Creswell technique. The results showed that the three aspects of hardiness—commitment, control, and challenge—play an important role in shaping mothers' coping strategies. Mothers with high hardiness tend to use a combination of problem-focused coping and emotion-focused coping strategies adaptively. Hardiness also enables mothers to manage their emotions, remain empowered in decision-making, and view challenges as opportunities for growth. The coping strategies formed are not only situational, but also develop along with the mother's experience in parenting her child. Thus, hardiness plays a role as a psychological foundation that supports mothers' resilience in the long term. The practical implications can be used as a basis for developing psychological assistance programs based on strengthening hardiness so that mothers can undergo parenting in a more resilient and meaningful way. AbstrakMengasuh anak dengan Autism Spectrum Disorder (ASD) menimbulkan tantangan emosional dan praktis yang signifikan bagi ibu sebagai pengasuh utama. Penelitian ini bertujuan untuk menggambarkan hardiness pada ibu yang memiliki anak dengan ASD serta menjelaskan kontribusi hardiness terhadap strategi coping yang digunakan dalam menghadapi tantangan pengasuhan. Penelitian menggunakan pendekatan kualitatif fenomenologis dengan tiga orang ibu sebagai subjek, yang dipilih melalui teknik purposive sampling. Data diperoleh melalui wawancara mendalam dan dianalisis menggunakan teknik Creswell. Hasil penelitian menunjukkan bahwa ketiga aspek hardiness—komitmen, kontrol, dan tantangan—berperan penting dalam membentuk strategi coping ibu. Ibu dengan hardiness tinggi cenderung menggunakan kombinasi strategi problem-focused coping dan emotion-focused coping secara adaptif. Hardiness juga memungkinkan ibu untuk mengelola emosi, tetap berdaya dalam mengambil keputusan, serta melihat tantangan sebagai peluang untuk bertumbuh. Strategi coping yang terbentuk tidak hanya bersifat situasional, tetapi berkembang seiring pengalaman ibu dalam mengasuh anaknya. Dengan demikian, hardiness berperan sebagai fondasi psikologis yang mendukung ketahanan ibu dalam jangka panjang. Implikasi praktisnya dapat dijadikan dasar dalam pengembangan program pendampingan psikologis berbasis penguatan hardiness agar ibu dapat menjalani pengasuhan secara lebih resilien dan bermakna.